Sustainable Energy Recovery From the Malaysian Coal Bottom Ash and the Effects of Fineness in Improving Concrete Properties - Beddu, Salmia; Abd Manan, Teh Sabariah Binti; Mohamed Nazri, Fadzli; Kamal, Nur Liyana Mohd; Mohamad, Daud; Itam, Zarina; Ahmad, Mushtaq (Frontiers in Energy Research, 2022)
The particle size (µm) of coal bottom ash displayed significant effects on the concrete engineering properties. This research aims to assess the improvement of engineering properties of concrete containing CBA (fineness: 75 and 100 µm) known as Mix 75 and Mix 100, and to optimize the percentage of coal bottom ash as supplementary cement materials in concrete. The physicochemical properties of coal bottom ash were analyzed using X-ray fluorescence, X-ray diffraction, particle size distribution (PSD), and a scanning electron microscope. The strength of concrete was determined based on workability and compressive and splitting tensile strengths. The concrete strength improvement was optimized by response surface methodology. The results of the study showed that coal bottom ash was rich in silicates based on the highest peak at 45°. The scanning electron microscope images showed that coal bottom ash has few cenospheres and components of irregular-shaped char particles. The splitting tensile strengths in 28 curing days gradually decreased with an increase in coal bottom ash. The optimal percentage of coal bottom ash in Mix 75 is equivalent to 6% within 45.4 curing days producing 40 MPa of compressive strength. Meanwhile, the optimal percentage of CBA in Mix 100 is equivalent to 12% within 56 curing days producing 50 MPa of compressive strength. The future works needed to extend the experimental observations are the economic analysis and effect of the greenhouse reduction on the usage of CBA in building infrastructure.